2008
DOI: 10.1186/1754-1611-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Backscattering particle immunoassays in wire-guide droplet manipulations

Abstract: A simpler way for manipulating droplets on a flat surface was demonstrated, eliminating the complications in the existing methods of open-surface digital microfluidics. Programmed and motorized movements of 10 μL droplets were demonstrated using stepper motors and microcontrollers, including merging, complicated movement along the programmed path, and rapid mixing. Latex immunoagglutination assays for mouse immunoglobulin G, bovine viral diarrhea virus and Escherichia coli were demonstrated by merging two drop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…It has been demonstrated that WDM could be used for repeated movement and merging of 5-20 μL droplets on a superhydrophobic surface [16]. This is possible because the work of adhesion of a 10 μL droplet to a superhydrophobic surface (θ ¼ 155 ) is 14 nJ, which is overcome by the work of adhesion to a metal wire (θ ¼ 10 ) of 57 nJ.…”
Section: Particle Immunoassaymentioning
confidence: 98%
See 2 more Smart Citations
“…It has been demonstrated that WDM could be used for repeated movement and merging of 5-20 μL droplets on a superhydrophobic surface [16]. This is possible because the work of adhesion of a 10 μL droplet to a superhydrophobic surface (θ ¼ 155 ) is 14 nJ, which is overcome by the work of adhesion to a metal wire (θ ¼ 10 ) of 57 nJ.…”
Section: Particle Immunoassaymentioning
confidence: 98%
“…These methods include electrowetting-on-dielectric (EWOD) [4,5], magnetofluidics [6,7], magnetofluidics with surface energy trapping [8,9], electrospun fiber mats [10], light-induced dielectrophoresis [11], optical trapping [12], pneumatic actuation on a thin superhydrophobic membrane [13], actuation by vibration [14], heater controlled surface tension gradients known as thermocapillary forces [15], and wireguided droplet manipulation (WDM) [1,[16][17][18]. The high degree of interest in developing new droplet manipulation technologies follows from their importance in advancing molecular biology and its applications.…”
Section: Droplet Manipulation In Molecular Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been a number of optical approaches with microfluidic devices including surface enhanced Raman scattering, interferometry, and particle beam emission spectroscopy [12][13][14], little effort has been made Keesung Kim 1,2 Man-Bock Gu toward the development of light scattering detection inside a microfluidic device [15,16]. In this sense, the so-called ''light scattering particle immunoagglutination assay'' (LSPIA) could be a new, alternative method for rapid and high-sensitivity detection of proteins, viruses and bacteria [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…To manipulate the droplets, paramagnetic micro/nanoparticles are often incorporated into the droplets to impart them with a magnetic responsive ability (Egatz-Gomez et al 2006Lindsay et al 2007;Garcia et al 2007;Guo et al 2006;Schneider et al 2008;Bormashenko et al 2008). A guiding wire that directly contacts with the droplet was also employed to direct the droplet movement (Mumm et al 2009;Yoon and You 2008). In addition, surface tensioninduced pressure gradient was used to drive the droplet movement on a superhydrophobic surface (Hong and Pan 2011).…”
Section: Introductionmentioning
confidence: 99%